Reliability and concurrent and construct validity of the Strategies for Weight Management measure for adults. Issue 3 (May 2016) - Kolodziejczyk, Julia K.; Norman, Gregory J.; Rock, Cheryl L.; Arredondo, Elva M.; Roesch, Scott C.; Madanat, Hala; Patrick, Kevin
Summary: Introduction: This study evaluates the reliability and validity of the strategies for weight management (SWM) measure, a questionnaire that assesses weight management strategies for adults. The SWM includes 20 items that are categorized within the following subscales: (1) energy intake, (2) energy expenditure, (3) self-monitoring, and (4) self-regulation. Methods: Baseline and 6-month data were collected from 404 overweight/obese adults (mean age = 22 ± 3.8 years, 68% ethnic minority) enrolled in a randomized controlled trial aiming to reduce weight by improving diet and physical activity behaviours. Reliability and validity were assessed for each subscale separately. Cronbach alpha was conducted to assess reliability. Concurrent, construct I (sensitivity to the study treatment condition), and construct II (relationship to the outcomes) validity were assessed using linear regressions with the following outcome measures: weight, self-reported diet, and weekly energy expenditure. Results: All subscales showed strong internal consistency. The strength of the validity evidence depended on subscale and validity type. The strongest validity evidence was concurrent validity of the energy intake and energy expenditure subscales; construct I validity of the energy intake and self-monitoring subscales; and construct II validity of the energy intake, energy expenditure, and self-regulation subscales. Conclusions: Results indicate that the SWM can be used to assess weight management strategies among an ethnically diverse sample of adults as each subscale showed evidence of reliability and select types of validity. As validity is an accumulation of evidence over multiple studies, this study provides initial reliability and validity evidence in one population segment.